New Approach to Early Gestosis Therapy - Kudrevich, I. A. (Problems of Cryobiology and Cryomedicine, 2006)
The examination and treatment of pregnant women with early gestosis (vomiting) in pregnancy terms of 5-14 weeks were carried-out. Basing on biochemical investigations a high efficiency of cryopreserved preparations in a combined treatment of this pathology was proved.